Surgical Site Infections by Mycobacterium after Cesarean Section in Bangladesh: A Case Report (Bangladesh Journal of Infectious Diseases, 2015)
Surgical site infection is very common in Bangladesh which is due to several reasons. During caesareansection it is not unlikely that this type of infection can be happened. In addition to the common bacteriaatypical bacteria sometimes causes the surgical site infection like Mycobacterium species. In this casereport a cesarean section-acquired Mycobacterium surgical site infections has been reported in Bangladeshwhich was presented as repeated abscess formation at the site of the caesarean section. Pus was drainedfrom the abscess and Zeil-Neelsen staining was performed and was found slender rod, beaded appearance Acid-fast bacilli. Then the patient was treated with anti-tubercular drugs and was totally cured.Bangladesh J Infect Dis 2014;1(1):18-21